Produção de cartilha sobre infecções sexualmente transmissíveis e gravidez na adolescência de forma colaborativa com alunos do ensino médio - Albuquerque, Lívia dos Santos Andrade de (2019)
Sexually transmitted infections (STI) are increasingly affecting the world's population, especially the age group of adolescents. These illnesses as well as an unwanted pregnancy can be easily avoided through the use of methods already known by the most part of adolescents, but not commonly used by them, because of many different factors amongst the lack of encouragement from the family, the school environment or only for a cultural point of view. In addition to STI, another major public health problem is the large number of pregnant adolescents in Brazil, especially in the state of Rio de Janeiro, where the study takes place. The school as a health promoter can bring significant results in the quality of life of this individual in adulthood and may even reduce the chain of transmission of these diseases. This study aimed to elaborate and apply a didactic sequence aimed at students' understanding of the prevention of sexually transmitted infections and teenage pregnancy. After the application of the didactic schedule, the students were stimulated and showed themselves able to share what they learned through the production of an educational booklet on the subject. The booklet is also a product of this study that can be used inside the school as an instrument of debate among other students. The whole construction of knowledge was based on an investigative teaching in search of meaningful learning, where the student not only repeats concepts, but learns how to apply what he has learned in his daily life. The study was relevant because the students were able to exercise the research, the debate with their classmates of the same age group and they have learned important concepts about human reproduction issues besides several methods of preventing infections. In the end they were able to pass on the knowledge acquired.